Multiple mosquito AMPs are needed to potentiate their antifungal effect against entomopathogenic fungi - Ramirez, José L.; Hampton, Kylie J.; Rosales, Alayna M.; Muturi, Ephantus J. (Frontiers in Microbiology, 2023)
Mosquito resistance to microbial infections, including fungal entomopathogens that are selected for mosquito control, depend on a range of antimicrobial effectors, among them antimicrobial peptides (AMPs). These short peptides, along the antimicrobial effector lysozyme, act by disrupting the microbial cell membrane or by interfering with microbial physiological processes. While the induction of AMPs and lysozyme during fungal entomopathogenic infections have been reported, their contribution to the mosquito antifungal response has not been evaluated. In this study, we assessed the induction of Ae. aegypti AMPs and lysozyme genes at two points of infection and against distinct entomopathogenic fungi. Our results indicate that fungal infection elicits the expression of cecropin, defensin, diptericin, holotricin and lysozyme, but do not affect those of attacin or gambicin. We further evaluated the role of these antimicrobial effectors via RNAi-based depletion of select AMPs during challenges with two entomopathogenic fungi. Our results reveal that AMPs and lysozyme are critical to the antifungal response, acting in concert, rather than individually, to potentiate their antimicrobial effect against entomopathogenic fungi. This study further contributes to a better understanding of the mechanisms that confer resistance to entomopathogenic fungi in an important mosquito vector.